2020
DOI: 10.1155/2020/8824757
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Aplasia Cutis Congenita Encircling the Trunk Associated with Fetus Papyraceus

Abstract: Aplasia cutis congenita associated with fetus papyraceus, though rare, is well known. On the other hand, aplasia cutis congenita associated with fetus papyraceus presenting with symmetrical circumferential scarring encircling the trunk has not been previously reported. Herein, we report a 2-month-old girl with symmetrical circumferential scarring encircling the trunk associated with fetus papyraceus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The above-mentioned cases of extensive ACC with truncal involvement were classified as Group V ACC,32–35 38 even though two of them, namely Boente et al 32 and Effendi et al ,38 did not have a history of fetus papyraceous or vanishing twin, as was the case in our patient. In these cases, the lesion had a highly characteristic, symmetric distribution pattern that encircled the umbilicus and formed an ‘H’ pattern on the anterior or posterior trunk, which was very similar to the presentation in our patient.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The above-mentioned cases of extensive ACC with truncal involvement were classified as Group V ACC,32–35 38 even though two of them, namely Boente et al 32 and Effendi et al ,38 did not have a history of fetus papyraceous or vanishing twin, as was the case in our patient. In these cases, the lesion had a highly characteristic, symmetric distribution pattern that encircled the umbilicus and formed an ‘H’ pattern on the anterior or posterior trunk, which was very similar to the presentation in our patient.…”
Section: Discussionmentioning
confidence: 56%
“…In terms of the extent of involvement, to the best of the authors’ knowledge, our patient possibly has one of the largest extent in the reported literature, among surviving patients with ACC. Although there are numerous case reports of ACC, only a handful describe ‘extensive ACC’, including seven that involve the scalp,21 26–31 four that affect the trunk,32–35 and three that affect both the head and trunk . Among these, only the latter three36–38 are nearly as extensive as our patient, with only one of them having survived 38.…”
Section: Discussionmentioning
confidence: 99%